Sustainable Development – How to Recognize Integrated Order - Borys, Tadeusz (Problemy Ekorozwoju, 2011)
The subject of these considerations is to show the role of integrated order category in refinement of the new paradigm of development. This paradigm is being introduced as sustainable, durable, self-sustaining, or eco-development. The article is trying to answer two important questions: first – Is sustainable development as legal representative of this new paradigm enough developed concept of development? Secondly – what is the role of integrated order in this refinement? Integrated order is here understood as benchmarking essence of sustainable development, as positive target of developmental changes merging in consistent way different orders: economic, social (including institutional-political) and environmental (including spatial). As minimal axiological level of orders formation moderate anthropocentrism was indicated. Ways of consideration and decoding sustainable development as integrated order vary depending on scientific field and discipline. The article is showing this phenomenon on the example of few scientific research centers.